(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comparative analysis of the concepts of "digital education" and "digital culture", their definitions, and their specific characteristics. At the same time, the article also examines the philosophical and social aspects of these concepts.